Accountable behavior towards sustainable development: the role of knowledge and attitude of university graduates / Norlaila Md Zin ... [et al.] - Md Zin, Norlaila; Kasim, Eley Suzana; Mohamed Azmi, Nur 'Iishah; Al-Dhubaibi, Ahmed Abdullah Saad; Zainal, Nurazilah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Although many studies have examined sustainability from the organisational corporate viewpoint, limited studies have focussed on the role of individual accountable behaviour in supporting sustainable development agenda. Studies have shown that knowledge and attitude of individuals are essential requirement to achieve sustainable development. However, little is known on how university graduates' knowledge and attitude contribute to accountable behaviour. Given that university graduates are viewed as agents of change, this study aimed to examine the effect of knowledge and attitude on their accountable behaviour. This study collected data through quantitative survey involving 385 university graduates from various universities in Malaysia. To gain a deeper understanding of the research issues and to follow up on the queries of the open-ended survey, we conducted qualitative interviews with five university graduates. The outcome revealed that both knowledge and attitude significantly influenced accountable behaviour towards sustainable development. These findings add to the body of knowledge founded on Malaysia's reality as a developing nation seeking to advocate sustainable development.